A Review of Cisplatin-Associated Ototoxicity - Paken, Jessica; Govender, Cyril D.; Pillay, Mershen; Sewram, Vikash (Seminars in Hearing, 2019)
Cisplatin, an effective antineoplastic drug used in the treatment of many cancers, has ototoxic potential, thus placing cancer patients, receiving this treatment, at risk of hearing loss. It is therefore important for health care professionals managing these patients to be aware of cisplatin's ototoxic properties and its clinical signs to identify patients at risk of developing a hearing impairment. Eighty-five English peer-reviewed articles and two books, from January 1975 to July 2015, were identified from PubMed, ScienceDirect, and EBSCOhost. An overview of cisplatin-associated ototoxicity, namely its clinical features, incidence rates, molecular and cellular mechanisms, and risk factors, is presented in this article. This review further highlights the importance of a team-based approach to complement an audiological monitoring program in reducing any further loss in the quality of life of affected patients, as there is currently no otoprotective agent routinely recommended for the prevention of cisplatin-associated ototoxicity.
Keywords: cisplatin; ototoxicity; hearing loss; ototoxicity monitoring program; cancer; otoprotectant